Discovery of Stable Peers in a Self-Organising Peer-to-Peer Gradient Topology - MEIER, RENE (Springer-Verlag, 2006)
Peer-to-peer (P2P) systems are characterised by a wide disparity in peer resources and capabilities. In particular, a number of measurements on deployed P2P systems show that peer stability (e.g. uptime) varies by several orders of magnitude between peers. In this paper, we introduce a peer utility metric and construct a self-organising P2P topology based on this metric that allows the efficient discovery of stable peers in the system. We propose and evaluate a search algorithm and we show that it achieves significantly better performance than random walking. Our approach can be used by certain classes of applications to improve the availability and performance of system services by placing them on the most stable peers, as well as to reduce the amount of network traffic required to discover and use these services. As a proof-of-concept, we demonstrate the design of a naming service on the gradient topology.
PUBLISHED
Keywords: Computer science; Peer-to-peer (P2P)